1999
DOI: 10.1002/(sici)1097-0215(19990531)81:5<730::aid-ijc11>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of angiogenesis as a mechanism for inhibition by L?-hydroxyvitamin D3 and 1,25-dihydroxyvitamin D3 of colon carcinogenesis induced by azoxymethane in Wistar rats

Abstract: The effects of 1α‐hydroxyvitamin D3[1α(OH)D3] and 1,25‐dihydroxyvitamin D3[1,25(OH)2D3] on the incidence of colon tumors induced by azoxymethane and on the labeling index and angiogenesis of colon tumors were investigated in Wistar rats. Rats received 10 weekly injections of 7.4 mg/kg body weight of azoxymethane and i.p. injections of 1α(OH)D3 and 1,25(OH)2D3 at lower and higher doses every other day for 45 weeks. Prolonged administration of both 1α(OH)D3 and 1,25(OH)2D3 at a higher dose significantly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(74 citation statements)
references
References 13 publications
0
73
0
Order By: Relevance
“…1a25(OH) 2 D 3 modulates the angiogenic phenotype of SW480-ADH cells 1a,25(OH) 2 D 3 has been previously shown to block angiogenesis (Iseki et al, 1999). This effect may stem from the modulation of the expression profile of key regulators of vascularization produced by the tumor cells.…”
Section: Id1 and Id2 Genes Are Differentially Expressed In Colon Carcmentioning
confidence: 99%
See 2 more Smart Citations
“…1a25(OH) 2 D 3 modulates the angiogenic phenotype of SW480-ADH cells 1a,25(OH) 2 D 3 has been previously shown to block angiogenesis (Iseki et al, 1999). This effect may stem from the modulation of the expression profile of key regulators of vascularization produced by the tumor cells.…”
Section: Id1 and Id2 Genes Are Differentially Expressed In Colon Carcmentioning
confidence: 99%
“…In animal models 1a,25(OH) 2 D 3 treatment causes significant decrease in tumor microvessel density (Iseki et al, 1999;Mantell et al, 2000;Bernardi et al, 2002). The effect of 1a,25(OH) 2 D 3 on tumor angiogenesis is a sum of hormone-induced changes in the angiogenic profile of tumor cells and direct 1a,25(OH) 2 D 3 effects on endothelial cells.…”
Section: Id1 and Id2 Genes Are Differentially Expressed In Colon Carcmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was recently shown that vitamin D was a potent inhibitor of angiogenesis by its effects on endothelial cells 34 and by interrupting signaling pathways that are key to angiogenesis, specifically in tumorigenesis. 35,36 The primary purpose of this study was to examine the relationship between serum vitamin D levels and AMD. We hypothesized that individuals in the highest quintile of serum vitamin D levels would have a lower prevalence of AMD compared with those in the lowest quintile.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue sections showed that granules of blown yellow to blow color present in cytoplasm were positive markers. In terms of Iseki K criteria (Iseki et al, 1999), an comprehensive assessment was conducted according to the staining intensity and the number of positive cells and converted into the positive index: a staining intensity (0=none, 1=weak, 2= moderate, 3= strong); b number of positive cells (0=0 to 5% positive staining cells, 1=5% to 50% positive staining cells, 2=50% to 100% positive staining cells). If the total score of a and b was 0 to 1, the positive index was 0; If the total score of a and b was 2, the positive index was 1; If the total score of a and b was 3, the positive index was 2; If the total score of a and b was 4 or 5, the positive index was 3.…”
Section: Results Assessment Criteriamentioning
confidence: 99%